El lenguaje radial - Vega Cotrina, Medaly (2021)
The radio has a particular way of narrating, it has its own language that is not only the _x000D_ Word, through sound it possible to generate in the human mind, representations of what _x000D_ is heard and that is where the radio uses its main elements: voice, music, sound efects _x000D_ and even silence. Thus, radio lenguaje combines sound and non-sound resources that _x000D_ influence the imaginative-visual process in the listener._x000D_ As one of the important elements of radio language, sonore aspects souch as diction, _x000D_ intonation, rhythm, pauses, tone must be considered in the voice. The second element, _x000D_ music, help us organize and propose a suggestive environment for the situacion. The _x000D_ third element, the sound effects, serve to describe the actions. And as the last optional _x000D_ element in the classification of the elements, silence the suspense, intrigue or pause.